Reap exceptional value from M&A;: manage it as a core competence - Galpin, T (Emerald Publishing Limited, 2018)
Purpose: Mergers and acquisitions (M&As) have become the preferred growth strategy for many executives. However, simply “doing deals” is not enough to create a competitive advantage for their companies. Only focusing on M&A as a financial transaction is too narrow of an approach, which is easily duplicated across firms. Using Woodward, Inc. as a case example, this article shows how using an actionable, end-to-end process model, and embedding integrated capabilities within the organization, across the entire process, managers can make M&A a core competence to provide a valuable, rare, and inimitable advantage for their firms. Design/methodology/approach: A mixed-methods approach, combining action research with a narrative synthesis of empirical and practice literature was used to develop a comprehensive M&A process model - the Deal Flow Model - consisting of ten stages across three phases. The resource-based view, core competencies, and the VRIO framework provide a theoretical foundation for the model. An application of the Deal Flow Model using Woodward Inc. as a case example is also presented. Findings: Only focusing on M&A as a financial transaction is too narrow of an approach, which is easily duplicated across firms. Instead, using an actionable, end-to-end process model, and embedding integrated capabilities within the organization across the entire M&A process provides a valuable, rare, and inimitable advantage for firms. Research limitations/implications: Researchers will find the Deal Flow Model useful as a structure to examine the M&A process as a whole or to frame single-stage, single-discipline research in the broader context of the overall M&A process. Practical implications: A practice-oriented Deal Flow Model, providing a cross-disciplinary, end-to-end view of the M&A process is presented. The model is designed to be actionable by managers, who can apply the process to build the M&A competence of their organization. Originality/value: The Deal Flow Model is unique as it is designed to be actionable by managers, who can apply the process to build the M&A competence of their organization. Likewise, researchers will find the model useful as a structure to examine the M&A process as a whole or to frame single-stage, single-discipline research in the broader context of the overall M&A process.